2006
DOI: 10.1348/000709905x63768
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perceptions of remediation possibilities of Dutch students in special education

Abstract: Special education teachers may also hold an image of the 'ideal' student. Students with high academic achievement levels are perceived as having fewer behavioural problems and more highly involved parents than students with low academic achievement levels. Whether this is due to justified or unjustified teachers' perceptions is a matter for future research. What is important is that stereotyping of students (justly or not) poses a serious problem for the Dutch reintegration policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…According to the earlier studies, teachers seem to be good informants in evaluating children’s SLDs (e.g., Avchen, Scott, & Mason, 2001; Mannerkoski et al, 2006), even though it has been reported that teachers may overestimate children’s problems (Ahonen & Lyytinen, 1998). Also, several factors like preconceptions and stereotypes affect teachers’ assessments (Bakker & Bosman, 2006; Sideridis, Antoniou, & Padeliadu, 2008). Furthermore, the screening instrument for SLDs was also a weakness.…”
Section: Discussionmentioning
confidence: 99%
“…According to the earlier studies, teachers seem to be good informants in evaluating children’s SLDs (e.g., Avchen, Scott, & Mason, 2001; Mannerkoski et al, 2006), even though it has been reported that teachers may overestimate children’s problems (Ahonen & Lyytinen, 1998). Also, several factors like preconceptions and stereotypes affect teachers’ assessments (Bakker & Bosman, 2006; Sideridis, Antoniou, & Padeliadu, 2008). Furthermore, the screening instrument for SLDs was also a weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Hipwell et al 2002;Tarren-Sweeney, Hazell and Carr 2004;Lucia and Breslau 2006). Expectancy biases are recognised as important to teachers' interpretation of behaviour (Darley and Fazio 1980) (for example, through pupils' attitudes (Araujo 2005), attainment (Bakker and Bosman 2006), age (Borg andFalzon 1990, 1993), race (Stevens 1980;Zimmerman et al 1995), gender (Condry and Ross 1985;Maniadaki, Sonuga-Barke and Kakouros 2003;Munn, Johnson and Sharp 2004) and socioeconomic status (Childs and *Corresponding author. Email: mw244@cam.ac.uk Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…(Bakker & Bosman, 2006;Kelly et al, 2007 .äGQÉÑYh OÉ©HC G øe ¿ÉàãMÉÑdG É¡H âeÉb »àdG á«YÓ£à°S'G á°SGQódG äÓµ°ûe" ƒgh ∫hC 'G ó©ÑdG :»JB 'Éc OÉ©HC G áKÓK πã" IQÉÑY (36) øe áfÉÑà°S'G âfƒµJ óbh º∏©ŸÉH ≥∏©àJ äÓµ°ûe" ƒgh ÊÉãdG ó©ÑdGh ,äGQÉÑY 9 øe ¿ q ƒµJh "¥É©ŸG ÖdÉ£dÉH ≥∏©àJ øe ¿ q ƒµJh ,"á°SQóŸÉH ≥∏©àJ äÓµ°ûe{ πãÁh ådÉãdG ó©ÑdGh ,IQÉÑY 12 øe âf q ƒµJh ,z√OGóYE Gh :»JB 'G ƒëaedG ≈∏Y »°SɪN áHÉLE G èjQóJ ≥ah ¢SÉ«≤ŸG Gòg äGQÉÑY øY áHÉLE 'G ºàJh . ,24 ,23 ,21) »g äGQÉÑY 9 ¬«∏Y â©Ñ°ûJ óbh (á°SQóŸÉH ≥∏©àJ äÉHƒ©°U) ådÉãdG πeÉ©dG í°Vƒj (1) ºbQ ∫hó÷G .1^8 øeÉc QòéH %20 πeÉ©dG Gòg öùa óbh (36 ,34 ,30 ,29 ,26 ,22 .…”
unclassified